2020
DOI: 10.1038/s41598-020-66569-7
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism of strain transfer in polycrystals

Abstract: At the grain boundaries of plastically deforming polycrystals, strain transfer mechanisms can accommodate the shear strain carried by slip bands and mechanical twins to prevent stress build-ups and damage. So far, only the accommodation obtained through slip (and twinning) alone has been considered in the mechanism known as slip (and twin) transfer. Here, a strain transfer mechanism that also requires the rotation of the crystal lattice is demonstrated. A region of accumulated slip develops perpendicular to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…9(f). This latter strain transfer mechanism has been characterised extensively by the authors in a recent publication [31].…”
Section: Plastic Flow At Applied Stresses Above the General Yield Stressmentioning
confidence: 99%
“…9(f). This latter strain transfer mechanism has been characterised extensively by the authors in a recent publication [31].…”
Section: Plastic Flow At Applied Stresses Above the General Yield Stressmentioning
confidence: 99%
“…Finally, strain will accumulate where the higher amount of slip systems is found. This corresponds mostly to triple junctions and grain boundaries, as pointed out in subsection 3.2, where it has been shown that internal stresses are the highest [13,14] and more systems are required to accommodate the deformation [26,69].…”
Section: Application To a Magnified Regionmentioning
confidence: 96%
“…Also, the slip transfer behavior at the grain boundary played a significant role in governing the mechanical properties of polycrystals (Bieler et al, 2014; Sun et al, 2019). Since the stress build-ups and damage of the grain boundary were mainly attributed to the shear strain ( ε xy ) caused by the slip bands or mechanical twins (Di Gioacchino et al, 2020), the present study on slip transfer here mainly started from the ε xy map shown in Figure 10d. The m ′ of each grain boundary was calculated based on the activated slip systems of associated grains (see Table 1) is shown in Figure 10d marked with light blue or yellow digitals.…”
Section: Case Study: Slip Transfer Behavior In Pure Ti Platementioning
confidence: 99%